1989
DOI: 10.1149/1.2096408
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Defects in Semi‐Insulating GaAs and Their Effect on the FET Device Performance

Abstract: Epitaxial layers were grown on semi-insulating LEC GaAs substrates by the chloride CVD technique and depletion type MESFET's with a gate length of 0.5 am have been fabricated on these epitaxial layers. Correlation between the FET device performance and the substrate quality has been studied. It was found that the substrate quality largely affects the device performance. Dislocations of the substrate had no definite effect on the device performance, while the density of the precipitate-like microscopic defects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…These maybe achieved practically by g m compression. 41 The level of the conduction band with respect to the Fermi level is an important factor in determining whether normally-off operation is possible. Normally-off operation can be achieved when electron concentration [represented in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…These maybe achieved practically by g m compression. 41 The level of the conduction band with respect to the Fermi level is an important factor in determining whether normally-off operation is possible. Normally-off operation can be achieved when electron concentration [represented in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that subsurface defects could alter the performances of GaAs-based devices. [16] Additionally, because nanoscratching results in material displacement rather than material removal, it gives rise to hillock formations surrounding the features as well as debris within features. [14,17] The consequence is a much-increased surface roughness and a lack of control over the shape and edge-sharpness of the desired features.…”
Section: Introductionmentioning
confidence: 99%